Penguatan Good Governance dan Keamanan Informasi dalam Mendorong Organisasi Adaptif di Era Globalisasi Digital: Pengabdian - Willy Nurhayadi; Ria Puspitasari; Jamaludin Jamaludin; Ilma Darojat; Vernando Vernando; Tekni Megaster; Fida Arumingtyas; Eko Sudarmanto (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The rapid development of digital technology and globalization has encouraged organizations to enhance their adaptability through strengthening governance and information security. However, many organizations still face limitations in implementing good governance principles and managing information security effectively. This Community Service Program aims to improve participants’ understanding of the importance of good governance and information security in creating adaptive organizations in the era of digital globalization. The program was conducted online through Zoom Meeting and involved approximately 88 participants from various organizational and professional backgrounds. The implementation method consisted of preparation, implementation, evaluation, and follow-up stages using an educative-participatory approach through socialization, training, and interactive discussions. Program evaluation was carried out using pre-tests and post-tests to measure participants’ level of understanding before and after the activity. The results demonstrated a significant improvement in participants’ understanding, indicated by an increase in the average pre-test score from 68 to 86 in the post-test. In addition to enhancing participants’ literacy regarding organizational governance and information security, the program also increased awareness of the importance of digital risk management, data protection, and strengthening an adaptive organizational culture. Therefore, this community service activity provided a positive contribution to supporting the development of professional, secure, and responsive organizations in facing digital transformation.